Sales Growth as a Moderation of Liquidity and Company Size Against Tax Avoidance (Empirical Study of Mining Sector Companies on the Indonesian Stock Exchange) - Hastianingsih, Desy; Mareta, Sigit (DINASTI RESEARCH, 2024)
This research aims to determine the influence of Liquidity, Company Size and Sales Growth on Tax Avoidance in 2019-2022. This research method uses quantitative methods. The object of this research is secondary data obtained from financial reports on the Indonesian Stock Exchange for mining companies for the 2019-2022 period, where the technique applied is purposive sampling and using panel data. Based on the results of data processing using Eviews 13 show that liquidity has an effect on tax avoidance, company size has no effect on tax avoidance, sales growth influence on Tax Avoidance, Liquidity which is moderated by Sales Growth has no effect on Tax Avoidance, and Company Size which is moderated by Sales Growth has no effect on Tax Avoidance.